2010
DOI: 10.1016/j.sna.2010.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Scintillation particle detection based on microfluidics

Abstract: a b s t r a c t A novel type of particle detector based on scintillation, with precise spatial resolution and high radiation hardness, is being studied. It consists of a single microfluidic channel filled with a liquid scintillator and is designed to define an array of scintillating waveguides each independently coupled to a photodetector. Prototype detectors built using an SU-8 epoxy resin have been tested with electrons from a radioactive source. The experimental results show a light yield compatible with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…When used in a detector they make for an active medium with virtually no radiation aging, as the scintillator can be easily renewed by recirculating new liquid in the detector. Recent advancements in the field of liquid scintillation detectors were made with the introduction of microfluidic scintillation detectors [14]. Such device consists in a single microfluidic channel with a serpentine geometry, patterned by SU-8 photolithography, in which a scintillating liquid is injected.…”
Section: Single Layer Devicesmentioning
confidence: 99%
See 3 more Smart Citations
“…When used in a detector they make for an active medium with virtually no radiation aging, as the scintillator can be easily renewed by recirculating new liquid in the detector. Recent advancements in the field of liquid scintillation detectors were made with the introduction of microfluidic scintillation detectors [14]. Such device consists in a single microfluidic channel with a serpentine geometry, patterned by SU-8 photolithography, in which a scintillating liquid is injected.…”
Section: Single Layer Devicesmentioning
confidence: 99%
“…The high aspect ratio capabilities of SU-8 allowed to obtain narrow channel walls over a depth of 200 µm (Figure 4b), enabling a high fill-factor while keeping enough liquid thickness to produce and guide a light pulse with an efficacy comparable to small diameter scintillating fibres [15]. Thanks to the single-channel configuration, it is relatively easy to replace the liquid scintillator in the device, resulting in an increased radiation resistance.…”
Section: Single Layer Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, thin and light microfluidic devices in silicon are in development for bio-chemical applications [3], but the typical values of the flow rate and pressure are much lower with respect to what is required for detector cooling applications. In addition, the presence of a low temperature fluid and of a high radiation level is unique to the application in HEP detectors [4]. Preliminary studies of two-phase flow in silicon microchannels have already shown the potential advantages of such systems with respect to standard cooling of particle detectors [5].…”
Section: Introductionmentioning
confidence: 99%